Priming thermotolerance: unlocking heat resilience for climate-smart crops - Chopra, Priyanka; Sapia, Natalia; Karami, Omid; Kumar, Pawan; Honys, David; Colombo, Lucia; Mendes, Marta; Benhamed, Moussa; Fotopoulos, Vasileios; Lieberman-Lazarovich, Michal; Mueller-Roeber, Bernd; Kaiserli, Eirini; et al. (My University, 2025)
Rising temperatures and heat waves pose a substantial threat to crop productivity by disrupting essential physiological and reproductive processes. While plants have a genetically inherited capacity to acclimate to high temperatures, the thermotolerance capacity of many crops remains limited. This limitation leads to yield losses, which are further intensified by the increasing intensity of climate change. In this review, we explore how thermopriming enhances plant resilience by preparing plants for future heat stress (HS) events and summarize the mechanisms underlying the memory of HS (thermomemory) in different plant tissues and organs. We also discuss recent advances in priming agents, including chemical, microbial and physiological interventions, and their application strategies to extend thermotolerance beyond inherent genetic capacity. Additionally, this review examines how integrating priming strategies with genetic improvements, such as breeding and genome editing for thermotolerance traits, provides a holistic solution to mitigate the impact of climate change on agriculture. By combining these approaches, we propose a framework for developing climate-resilient crops and ensuring global food security in the face of escalating environmental challenges.This article is part of the theme issue 'Crops under stress: can we mitigate the impacts of climate change on agriculture and launch the 'Resilience Revolution'?'.
Keywords: crop resilience; global warming; heat stress; priming; thermomemory; thermotolerance